(untitled) (Al-Academy, 2026)
This research is concerned with studying the methods of designing letter painting By employing digital media The invention of writing and the appearance of the first letter in the history of mankind In the historical city of Warka,It is considered one of the most important cultural and cognitive achievements of the Sumerian civilization, It passed through multiple stages and form until reached it by writing in arabic calligraphy, which is considered one of the most beautiful scripts in the world, the most difficult to master, and the most diverse.As a result of digital developments in the fields of life and in Arabic calligraphy in particular, calligraphers and designers used multiple digital programs in designing and producing the digital letter painting. Because the letters of Arabic calligraphy have aesthetic, symbolic, and expressive properties in their creation and inspiration from the letters of Arabic calligraphy with a contemporary vision and keeping pace with modernity, leaving traditional contexts, and inventing modern and multiple methods. The researcher defined the problem of his research with the following question: What are the methods for designing letter painting by employing digital media?, for the period from (2000 - 2023 AD), Iraq and the Emirates.The second chapter included the theoretical framework, as the first section dealt with the methods of designing the digital letter painting. The second section included the design elements and foundations of the digital letter painting, then followed by indicators of the theoretical framework. The third chapter included the research procedures, the researcher adopted the descriptive approach (content analysis), while the fourth chapter included analyzing samples, presenting results and conclusions, recommendations and proposals